Design of a Compact Multi-Band Circularly Polarized Antenna for Tracking and Localization Applications - Shanmuka Rooban Gunasekaran; Nordiana Mohamad Saaid; Thennarasan Sabapathy; Muzammil Jusoh; Mohamed Nasrun Osman; Saidatul Norlyana Azemi; Siddarth Pichandi; Suresh Ponnan (Geviva Publisher, 2026)
This project is about designing a compact multi-band circularly polarized antenna for tracking and localization applications which is receiver type of antenna. Existing commercial GPS antenna uses 2 frequency bands which have linear polarization (LP), less robust to the future GPS receiver system. Thus, in this project, a multi-band circularly polarized antenna will be designed. The antenna is a multi-band type antenna since it is radiating at three GPS frequency bands. The antenna development starts with creating three different size of patch which is known as L1, L2 and L5. L5 (1.164GHz -1.189GHz) is the smallest frequency among those three, L2 (1.215GHz -1.240GHz) is the middle range frequency and the biggest frequency is L1 (1.563GHz -1.588GHz). The size of the antenna will be approximately 100mm by 50mm because it is a handheld receiver antenna hence it is required to be small in size. This antenna uses Rogers and FR-4 as the substrate and copper as the ground plane and patch of the radiating element. All the design and simulation results are conducted using CST Studio Suite 2016 software. Based on the result, it is shows that the antenna producing 3 different frequency band with all the return loss value is under -10 dB. It is also producing an omnidirectional radiation pattern with axial ratio less than 3dB. For polarization, the antenna is right hand circular polarization (RHCP) and producing a reasonable gain for GPS application.